2018
DOI: 10.1038/s41467-018-04399-y
|View full text |Cite|
|
Sign up to set email alerts
|

FGF signalling controls the specification of hair placode-derived SOX9 positive progenitors to Merkel cells

Abstract: Merkel cells are innervated mechanosensory cells responsible for light-touch sensations. In murine dorsal skin, Merkel cells are located in touch domes and found in the epidermis around primary hairs. While it has been shown that Merkel cells are skin epithelial cells, the progenitor cell population that gives rise to these cells is unknown. Here, we show that during embryogenesis, SOX9-positive (+) cells inside hair follicles, which were previously known to give rise to hair follicle stem cells (HFSCs) and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 59 publications
6
51
2
Order By: Relevance
“…We treated embryos with tamoxifen at E13.5‐E14.5, when Merkel cells had not yet been specified, and collected paws and back skins at E17.5 (Figure E). Immunofluorescence analysis showed that GFP staining was found in approximately 85% of KRT8(+) Merkel cells in the back skin (Figure F, G), which is consistent with our previous report that showed that Merkel cells originate from SOX9(+) precursor cells in the back skin . In contrast, KRT8(+) Merkel cells were not GFP(+) in the glabrous paw skin (Figure H, I; Figure C).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…We treated embryos with tamoxifen at E13.5‐E14.5, when Merkel cells had not yet been specified, and collected paws and back skins at E17.5 (Figure E). Immunofluorescence analysis showed that GFP staining was found in approximately 85% of KRT8(+) Merkel cells in the back skin (Figure F, G), which is consistent with our previous report that showed that Merkel cells originate from SOX9(+) precursor cells in the back skin . In contrast, KRT8(+) Merkel cells were not GFP(+) in the glabrous paw skin (Figure H, I; Figure C).…”
Section: Resultssupporting
confidence: 91%
“…We collected paws from Atoh1‐GFP pups at embryonic day (E) 14.5, E15.5, E16.5 and postnatal day (P) 0 and performed immunofluorescence analyses of ATOH1‐GFP and the keratin intermediate filaments 8 and 20 (KRT8 and KRT20, respectively) that are expressed in more mature Merkel cells . At E14.5, when Merkel cells were already formed inside of the hair placode of the back skin, we could not detect any ATOH1‐GFP(+), KRT8(+) or KRT20(+) Merkel cells in the mouse paw (Figure A). At E15.5, a few ATOH1‐GFP(+) and KRT8(+) Merkel cells were observed in the mouse paw (Figure B).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations